2023
DOI: 10.1186/s12964-023-01336-5
|View full text |Cite
|
Sign up to set email alerts
|

Implications of TDP-43 in non-neuronal systems

Hao Ke,
Kang Liu,
Baowei Jiao
et al.

Abstract: TAR DNA-binding protein 43 (TDP-43) is a versatile RNA/DNA-binding protein with multifaceted processes. While TDP-43 has been extensively studied in the context of degenerative diseases, recent evidence has also highlighted its crucial involvement in diverse life processes beyond neurodegeneration. Here, we mainly reviewed the function of TDP-43 in non-neurodegenerative physiological and pathological processes, including spermatogenesis, embryonic development, mammary gland development, tumor formation, and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…Beyond its well-documented involvement in neurodegenerative diseases, emerging evidence has highlighted the significance of TARDBP in various cancer pathways, indicating its potential as a biomarker for tumor progression and prognosis 3 - 7 . The protein's aberrant expression and mutations have been associated with altered cellular dynamics, promoting oncogenesis through the dysregulation of cell proliferation, apoptosis, and metastasis 8 - 10 . Studies have demonstrated that TARDBP can influence tumor microenvironment, angiogenesis, and immune escape mechanisms, thereby supporting the aggressive behavior of malignant cells 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond its well-documented involvement in neurodegenerative diseases, emerging evidence has highlighted the significance of TARDBP in various cancer pathways, indicating its potential as a biomarker for tumor progression and prognosis 3 - 7 . The protein's aberrant expression and mutations have been associated with altered cellular dynamics, promoting oncogenesis through the dysregulation of cell proliferation, apoptosis, and metastasis 8 - 10 . Studies have demonstrated that TARDBP can influence tumor microenvironment, angiogenesis, and immune escape mechanisms, thereby supporting the aggressive behavior of malignant cells 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…TARDBP's involvement in cancer appears to be multifaceted, influencing various hallmarks of cancer across different tumor types. In neurodegenerative conditions, TARDBP has been implicated in the regulation of neuronal cell death, highlighting its potential role in cell survival pathways that are often hijacked in cancer 10 , 19 , 20 . This pan-cancer analysis of TARDBP seeks to delineate its expression patterns, mutational landscape, and functional impacts across a broad spectrum of cancers, with a particular focus on HCC.…”
Section: Introductionmentioning
confidence: 99%